Knowledge of biomedical waste management amidst the clinical students of dental college, Tamilnadu State, India - A cross sectional observational study - Vanita Dattatraya Revankar; Chitra Ponnusamy; Anbarasu Subramanian; Assmee Mohammed Noon; Manoharan Subhashini; Mithunraja Saravanaraja (Wolters Kluwer Medknow Publications, 2023)
Background: The objective of study was to assess the knowledge and awareness of the management of biological waste (BMW) among undergraduate students of Dental College, Tamilnadu state. Materials and Methods: Among the students of Dental College in Tamilnadu state, India, a cross-sectional observational research was conducted. A pre-designed questionnaire was distributed to the students. Their expertise and awareness of managing biomedical waste were the variables that were investigated. Results: One hundred and eighty students were participated. The male to female ratio was 1:2, and the average age of responders was 19.76 ± 1.03 years. When it comes to information concerning the management of biomedical waste, an average of 60.33% were correct and 39.57% were incorrect. For their knowledge of the same, 81.35% were correct and 18.65% were incorrect. Conclusion: The findings indicated that students had a high degree of knowledge and understanding regarding the management of biomedical waste.